Gerakan Sosial dalam Aksi Penyelenggaraan Sekolah untuk Anak Miskin - Rahmat, Abdi (Masyarakat: Jurnal Sosiologi, 2014)
This article shows the importance of civil society in the implementation of a school for poor children that are seen in the context of the social structure and state policies. During this time, the implementation of the school for poor children—done by the civil society organization (CSO) in Indonesia—is often understood as a micro phenomenon regardless of the context of broader social structures. What they do in fact can not be separated from the context of the macro structure. To that end, the main argument of this paper using the framework of the concept of social movement that emphasizes the dynamics of CSO actors and providing education in the face of structural poverty problems that occur. In the early part, this paper outlines some of the dimensions of social movements in the implementation of the school for poor children that are characteristic of the CSO. Arguments will end with a description of the opportunities for the development and sustainability of the CSO movement. This article departs from the results of a qualitative research using case study as a strategy of inquriy. Data were collected through interviews, observation, and study of documents and analyzed with qualitative data analysis is enriched by an extensive literature study.